MAKANAN JAJANAN SEHAT LAYAK JUAL UNTUK MAKANAN TAMBAHAN DI POSYANDU - Siti Fathonah; Wahyuningsih; Sarwi; Romiyatun Mijiling A; Angga Pratiwi; Lia Maretiana Safitri; Laela Rahma Agustin (LP2M Universitas Hasanuddin, 2023)
Community service activities implemented at the Bendan Negisor posyandu are counseling on knowledge of healthy snacks, skills in processing healthy snacks, and making dry shoes worth selling with hermetic packaging technology. Bendan Ngisor Village, Semarang. The participants of the activity were 20 posyandu cadres. The processed products are purple sweet potato sentencing, purple sweet potato onde-onde dry soes mocaf flour, and mung bean flour. Snack food packaging activities are crucial to increase sales value and productive business to increase family income. Service activities show a significant increase in knowledge, with a pretest score of 78.3, a posttest score of 90.8, and an N-gain of 0.54. Effectiveness test with N-gain obtained 0.54, with a moderate level of effectiveness. Data analysis showed preferences in the category of very favored with details of the average score of purple sweet potato sentencing 7.7 and 7.8 purple sweet potato onde-onde, and 7.6 dry shoes. Assistance in processing dry soes is carried out with results that meet the criteria for dry soes. Hermitically packaged dry soes are equipped with labels worthy of sale and can be a source of family income. — Kegiatan pengabdian masayarakat yang diterapkan di posyandu Bendan Negisor adalah memberikan penyuluhan pengetahuan makanan jajanan sehat, keterampilan dalam mengolah makanan jajanan sehat, dan pembuatan soes kering layak jual dengan teknologi kemasan hermitis. Peserta kegiatan sebanyak 20 kader posyandu. Produk yang diolah adalah senteling ubi ungu, onde-onde ubi ungu dan soes kering tepung mocaf dan tepung kacang hijau. Kegiatan pengemasan makanan jajanan sangat penting untuk meningkatkan nilai jual dan usaha produktif untuk menambah penghasilan keluarga. Kegiatan pengabdian menunjukkan peningkatan pengetahuan yang signifikan dengan skor pretes 78.3 menjadi dan skor postes 90.8. Uji efektifitas dengan N-gain diperoleh 0,54, dengan efektivitas tingkat sedang. Hasil analisis kesukaan dalam kategori sangat disukai dengan rincian rerata skor senteling ubi ungu 7,7; dan onde-onde ubi ungu 7,8, dan soes kering 7,6. Pendampingan praktek mengolah soes kering dilakukan dengan hasil yang sudah memenuhi kriteria soes kering. Soes kering dikemas yang hermitis dilengkapi dengan label sehingga layak jual dan dapat menjadi sumber pendapatan keluarga.